IMPLIKASI REGULASI PASAR MODAL TERHADAP MOTIF MANAJEMEN LABA: PENGUJIAN BERBASIS TEORI PENSIGNALAN - , SANSALONI BUTAR BUTAR, Prof. Dr. Suwardjono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the motives of earnings management following series of regulation released by the Capital Market Supervisory Agency and Jakarta Stock Exchange in 2004 (hereafter, SK Bapepam-LK and BEJ). SK Bapepam-LK and BEJ contains rules and decrees which reiterated the criteria, functions and authority of the audit committee and board of commissioners to enhance public companies adherence to good corporate governance. This study argues that the increased board independence after the issuence of SK Bapepam-LK and BEJ has shifted earnings management motives from opportunistic motive to signalling motive. The board of commissioners are expected to play an effective role to prevent manajer from using accruals as a way to achieve personal gain at the expense of stockholders. However, as a representative of stockhloders, the board allow managers to engagage in earnings management if it is in the best interest of stockholders. The board encourage managers to make use of accruals items to convey corporate value. Therefore, it is predicted that after the release of SK Bapepam-LK and BEJ, the negative effect of board of commissioners on abnormal accruals are more pronounced and the predictive content of accruals with respect to future earnings are expected to increase. Furthermore, since signalling purposes often use accruals abnormal to inflate earnings, the predictive ability of positive abnormal accruals with respect to future earnings is predicted to increase after the realese of SK Bapepam and BEJ. The results of the study can be summarized as follows: 1). The negative influence the board of commissioners on earnings management is stronger after the isssuance of SK Bapepeam-LK dan BEJ than before they were issued. 2). The predictive content of abnormal accruals and positive abnormal accruals with respect to future earnings are stronger for 2004-2010 than that for 2001-2003. 4). The addition of independent members to become majority in the board does not alter the predictive content of accruals. Taken as a whole, the results indicate that SK Bapepam-LK and BEJ has successfuly increased the monitoring function of board commissioners, at least in the context of earning managements.